The Ethics of Learning that Influence Beneficial Knowledge from Az-Zarnuji's Perspective - Sholahuddin Qoffal (DIROSAT: Journal of Education, Social Sciences & Humanities, 2025)
Morality is the most important aspect in acquiring beneficial knowledge. When someone seeks knowledge while simultaneously applying moral values in their pursuit, such as respecting teachers and practicing daily habits, it is certain that the knowledge gained will be beneficial to the individual, even if the knowledge is limited. This research aims to examine in detail the influence of learning ethics according to Imam Az-Zarnuji on the usefulness of knowledge possessed by Tholibul Ilmi, referred to as ilmu nafi’ as explained in his work titled Ta’limul Muta’allim. The method used in this research is library research, which consists of two sources: the book Ta’limul Muta’allim as the primary source and secondary sources taken from library data such as papers, journals, and other library data. The results of this research are: 1) the ethics of learning as intended by Imam Az-Zarnuji are not only ethics during the learning process but ethics that encompass the daily life of students as long as they are still in the status of Tholibul Ilmi (students), 2) the ethics of learning explained by Imam Az-Zarnuji in his work greatly influence students to acquire beneficial knowledge (ilmu nafi’), 3) the ethics of learning explained by Imam Az-Zarnuji are part of the implementation of the knowledge possessed by students that can be categorized as ilmu nafi’. The benefit of this research is to provide a detailed explanation of the learning ethics intended by Imam Az-Zarnuji, so that it can serve as a foundation for students to acquire beneficial knowledge as hoped by Imam Az-Zarnuji.